Egypt, Greece and Rome - Freeman, Charles, 1947- (Oxford ; New York)
xvii, 759 s., [40] s. resim
Keywords: "Egypt, Greece, and Rome is regarded as one of the best general histories of the ancient world. It is written for the general reader and the student coming to the subject for the first time and provides a reliable and highly accessible point of entry to the period. Beginning with the early Middle Eastern civilizations of Sumer, and continuing right through to the Islamic invasions and the birth of modern Europe after the collapse of the Roman empire, the book ranges beyond political history to cover art and architecture, philosophy, literature, society, and economy. A wide range of maps, illustrations, and photographs complements the text. This third edition has been extensively revised to appeal to the general reader with several chapters completely rewritten and a great deal of new material added, including a new selection of images." --